2023
DOI: 10.1021/acs.inorgchem.2c03709
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Elusive Structure and Reactivity of Iron Boride α-FeB

Abstract: Crystal structures can strongly deviate from bulk states when confined into nanodomains. These deviations may deeply affect properties and reactivity and then call for a close examination. In this work, we address the case where extended crystal defects spread through a whole solid and then yield an aperiodic structure and specific reactivity. We focus on iron boride, α-FeB, whose structure has not been elucidated yet, thus hindering the understanding of its properties. We synthesize the two known phases, α-Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 63 publications
1
6
0
Order By: Relevance
“…However, MnB and FeB have both high-temperature FeB-type and low-temperature CrB-type polymorphs and can also form peculiar intergrowths of both CrB- and FeB- fragments when synthesized at lower temperatures. Similar cases of polymorphism are seen in other intermetallic compounds. …”
Section: Resultssupporting
confidence: 58%
“…However, MnB and FeB have both high-temperature FeB-type and low-temperature CrB-type polymorphs and can also form peculiar intergrowths of both CrB- and FeB- fragments when synthesized at lower temperatures. Similar cases of polymorphism are seen in other intermetallic compounds. …”
Section: Resultssupporting
confidence: 58%
“…18 keV, where the reaction media are sufficiently transparent to enable XRD detection in transmission mode through a capillary. We used a capillary oven setup inspired by a previous work. , To ensure homogeneity of the reaction medium, the capillary containing the reaction mixture was continuously scanned through 4 vertical positions. An XRD pattern was recorded at each position every 8.4 s with an acquisition time of 5 s. The same capillary oven used for in situ XRD was also used for in situ XAS at an energy corresponding to the K -edge of the probed element and in fluorescence detection mode, where X-ray fluorescence was collected from the capillary at an angle of ca.…”
Section: Resultsmentioning
confidence: 99%
“…Galvanic reactions of MAX and MAX-related phases occur at 400–700 °C, where it is difficult to probe reaction media in situ . In this context, in situ XRD and in situ X-ray absorption spectroscopy (XAS), which are sporadically used to probe molten salts, appear as ideal techniques to study the mechanisms of galvanic reactions of MAX and MAX-related phases. The combination of in situ XRD and in situ XAS to study molten salts is, however, not reported to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in the P 6/ mmm structures, the honeycomb, graphene-like, boron layer is sandwiched between two TM layers on both sides, with every TM atom located above or below the centroid of the honeycomb structure. Their bulk counterparts, all widely studied both experimentally and theoretically, are the ferromagnetic (FM) α and β modifications of FeB and the nonmagnetic (NM) CrB and ZrB compounds. The structure of α-FeB is debatable, whereas β-FeB and CrB are orthorhombic crystals with Pnma (no.…”
Section: Introductionmentioning
confidence: 99%
“…Their bulk counterparts, all widely studied both experimentally and theoretically, are the ferromagnetic (FM) α and β modifications of FeB and the nonmagnetic (NM) CrB and ZrB compounds. The structure of α-FeB is debatable, whereas β-FeB and CrB are orthorhombic crystals with Pnma (no. 62) and Cmcm (no.…”
Section: Introductionmentioning
confidence: 99%